2020
DOI: 10.3390/cancers12123760
|View full text |Cite
|
Sign up to set email alerts
|

MEK1 Inhibitor Combined with Irradiation Reduces Migration of Breast Cancer Cells Including miR-221 and ZEB1 EMT Marker Expression

Abstract: The miR-221 expression is dependent on the oncogenic RAS-RAF-MEK pathway activation and influences epithelial-to-mesenchymal transition (EMT). The Cancer Genome Atlas (TCGA) database analysis showed high gene significance for ZEB1 with EMT module analysis and miR-221 overexpression within the triple-negative breast cancer (TNBC) and HER2+ subgroups when compared to luminal A/B subgroups. EMT marker expression analysis after MEK1 (TAK-733) inhibitor treatment and irradiation was combined with miR-221 and ZEB1 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…The MAPK pathway is activated by a series of phosphorylation events that can be targeted through MEK, the downstream activator of MAPK. Trametinib and TAK-733 are small-molecule-selective MEK inhibitors with antitumor activity in cancers, such as gliomas, multiple myeloma, melanoma and triple-negative breast cancer [ 8 , 9 , 10 , 11 , 12 ]. Trametinib has recently been applied in clinical studies of brain tumors, suggesting that it has the ability to cross the blood–brain barrier (BBB) [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The MAPK pathway is activated by a series of phosphorylation events that can be targeted through MEK, the downstream activator of MAPK. Trametinib and TAK-733 are small-molecule-selective MEK inhibitors with antitumor activity in cancers, such as gliomas, multiple myeloma, melanoma and triple-negative breast cancer [ 8 , 9 , 10 , 11 , 12 ]. Trametinib has recently been applied in clinical studies of brain tumors, suggesting that it has the ability to cross the blood–brain barrier (BBB) [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…One study reported that radiation combined with an inhibitor of K-Ras/c-Raf/p38 signaling eliminated the metastatic potential of cervical cancers cells [28]. In addition, IR combined with treatment using a mitogen-activated protein kinase 1 inhibitor showed reduced breast-cancer cell migration [29]. For CRC, the pharmacological inhibition of phosphoinositide 3-kinase/AKT was shown to markedly enhance the cytotoxic effects of IR both in vitro and in vivo [30].…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs have been implicated in regulating the development and metastasis of human cancers. MiR221 is reported to be an oncogene in multiple cancers, including bladder cancer, breast cancer and thyroid cancer tumor cells [ 14 16 ]. The high expression of miR221 was correlated with the proliferation, invasion, and malignancy of thyroid cancer tumor cells [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The high expression of miR221 was correlated with the proliferation, invasion, and malignancy of thyroid cancer tumor cells [ 15 ]. The miR221/ZEB1 activity is efficiently targeted upon MEK1 inhibitor (TAK-733) treatment and when combined with irradiation treatment, significant reduction in migration of breast cancer cells was shown [ 16 ]. Likewise, in our study, miR221 expression was significant altered, and bioinformatic analysis revealed that annexin a1 might be a target for miR221 regulation.…”
Section: Introductionmentioning
confidence: 99%